2020
DOI: 10.2147/ott.s258357
|View full text |Cite
|
Sign up to set email alerts
|

<p>Biomarkers of Insulin and the Insulin-Like Growth Factor Axis in Relation to Breast Cancer Risk in Chinese Women</p>

Abstract: Background: The interplay between biomarkers of insulin and the insulin-like growth factor (IGF) axis in the context of breast cancer risk is unclear. Methods: We measured the concentrations of insulin, C-peptide, IGF1, and IGF binding protein 3 (IGFBP3) and calculated the homeostasis model assessment of insulin resistance (HOMA-IR) index and the IGF1/IGFBP3 ratio among 2536 patients with breast cancer and 2528 patients with benign breast disease recruited from Ruijin Hospital, Shanghai, China, between 2012 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Preclinical and clinical studies suggested complex associations between diabetes, especially type 2 diabetes with breast cancer ( 15 ). Our results showed that patients with breast cancer have significantly higher insulin levels than those without breast cancer, which is consistent with the previous evidence ( 7 ). As part of the important causes of diabetes, hyperinsulinemia and IR have been shown to be risk factors for breast cancer ( 4 7 , 16 ).…”
Section: Discussionsupporting
confidence: 93%
“…Preclinical and clinical studies suggested complex associations between diabetes, especially type 2 diabetes with breast cancer ( 15 ). Our results showed that patients with breast cancer have significantly higher insulin levels than those without breast cancer, which is consistent with the previous evidence ( 7 ). As part of the important causes of diabetes, hyperinsulinemia and IR have been shown to be risk factors for breast cancer ( 4 7 , 16 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, hyperinsulinemia associated with insulin resistance is also correlated with a high risk of breast cancer. Zhu et al (46) found that the OR for breast cancer associated with the highest quartile versus the lowest quartile of insulin was 1.45 (95% CI 1.20-1.75). Elevated insulin levels can cause high insulin growth factor-1 (IGF-1) bioavailability, leading to the occurrence and proliferation of breast cancer (10).…”
Section: Diabetes Mellitus and Breast Cancer Riskmentioning
confidence: 99%
“…Insulin is a key regulator hormone in cell growth and energy metabolism. Up-regulation of insulin secretion and insulin resistance results in elevated IGF-1 production and bioavailability, resulting in cell proliferation and tumor growth [ 25 ]. It should be noted that dietary insulin indices are related to insulin resistance [ 26 ].…”
Section: Discussionmentioning
confidence: 99%